POLA PENGOMBINASIAN TANAMAN DI KELOMPOK TANI HUTAN SEJAHTERA 4 DESA PESAWARAN TAMAN HUTAN RAYA WAN ABDUL RACHMAN - Adinda Azelia Ramadhani; Ceng Asmarahman; Indriyanto Indriyanto (Gorontalo Journal of Forestry Research, 2023)
The pattern of plant combinations is the arrangement of the species of plants that are cultivated in a field. This research aims to analyze the pattern of plant combinations in the arable land of KTH Sejahtera 4 Tahura Wan Abdul Rachman. The research method used is the multiple plot method, direct observation, and interviews. Plots are arranged systematically on the farmers' arable areas. The total area cultivated by KTH Sejahtera 4 Tahura Wan Abdul Rahcman farmers is 36.05 ha. The area of the sample plots made is 1,442 ha with a sampling intensity (IS) of 4%, therefore the number of plots made is 36 plots. The results showed that all farmers applied agroforestry techniques with mixed crop combinations at random. The combination combines MPTS plants, both from the forestry plant group and the agricultural plant group. From the results of the vegetation analysis, it is known that in KTH Sejahtera's arable land 4 plants that have a high level of dominance are cloves (Eugenia aromaticum L.) and nutmeg (Myristica fragrans). According to farmers' opinion, there are three types of plants that are superior, namely cocoa (Theobroma cacao), rubber (Hevea brasiliensis), and coffee (Coffea robusta L.). The plants favored by the farmers are the mainstay of their income.